Beyond rational choice theory: multifaceted determinants of participation in palm oil sustainable certification amongst smallholders in Malaysia - Ahmad Rizal, Ammar Redza; Md Nordin, Shahrina; Hussin, Siti Haslina; Hussin, Siti Rahayu (Frontiers Media, 2021)
The demand for palm oil is steadily increasing where global consumption in 2020 has reached 77 million metric tons or equivalent to 7 kg of palm per capita usage. However, the industry is under critics for unsustainable production practice and environmental degradation due to unscrupulous deforestation. One of the measures taken to ensure sustainability practices in the industry in Malaysia includes certifications such as the Roundtable on Sustainable Palm Oil (RSPO) and the Malaysian Sustainable Palm Oil (MSPO). These certifications are offered to industry players/plantation giants in which all stakeholders/members need to fulfill stringent requirements in order to obtain the certification. Efforts are now being taken to ensure that every stakeholder in the palm oil industry obtain sustainable certification, and this includes effort to enable smallholders to also follow the guidelines and fulfill the certification requirements. However, as of 2021, only 30% smallholders were certified despite the rigorous efforts made. Several factors may have hindered the participation of these smallholders. Hence, it is crucial that the agencies involved in managing this industry identify the factors influencing the certification of smallholders. The identification of these determinants will help policymakers to strengthen policy in disseminating sustainability practices in the palm oil industry. The objective of the current study is to identify factors influencing smallholders' participation in palm oil certification in Malaysia. This study looks beyond rational choice theory and develops a model based on elements of social structure and interaction. Quantitative approaches through questionnaire survey were used in this study. Purposive sampling was used, and data collections involved 200 oil palm smallholders in Malaysia. Four elements, namely, “Perceived Economic Benefit,” “Social Interaction,” “Shared Identity,” and “Communication Discourse,” were found to have significant influences on smallholders' participation in palm oil sustainable certification. Implication and future recommendation were included in the concluding remark.